Hubungan Iklim Kerja Dan Motivasi Berprestasi Dengan Kinerja Guru SMP Di Kecamatan Lasolo - . Ritmanto (Jayapangus Press, 2018)
This study aimed to analyze : (1) the correlation between work atmosphere and junior high school teacher’s performance in Lasolo sub regency; (2) the correlation between motivation for achievement and junior high school teacher’s performance in Lasolo sub regency; (3) the correlation between work atmosphere coupled with motivation for achievement and the performance of junior high school teachers in Lasolo sub regency. The research used a survey method, by applying a correlational approach. The population of the study was all teachers of junior high school in Lasolo sub regency, totaling 110. The sample of the study were 33 respondents who were selected through purposive random sampling technique. The data were collected through self-developed instrument, which was firstly piloted to empirically establish its validity and reliability. The result of the study: (1) there was a positively very significant correlation between work atmosphere and the performance of junior high school teachers in the sub regency of Lasolo, as was indicated by a coefficient correlation of 0,706. (2) There was a positively very significant correlation between motivation for achievement and the performance of junior high school teachers in the sub regency of Lasolo, as was indicated by a coefficient correlation of 0,661. and (3) there was a positively very significant correlation between work atmosphere coupled with motivation for achievement and the performance of junior high school teachers in the sub regency of Lasolo, as was indicated by a coefficient correlation (R) = 0,730 and determining coefficient (r square) = 0,533 or 53,3%.